PENGARUH VARIASI SUDUT DATANG DAN SUDUT TANGKAP CAHAYA PADA NILAI KONTRAS CITRA SPEKEL BERAS BERBASIS GUI MATLAB - Mahardika Mega Utama; Wiwis Sasmitaninghidayah (Komunikasi Fisika Indonesia, 2020)
Rice is the staple food of Indonesian. Rice quality is a factor that needs attention because it is related to consumer health.Checking the quality of rice using digital images can be applied because it is non-invasive, so the rice will be more hygienic. The method of utilizing digital images that can be used for checking the quality of rice is LSCI (Laser Speckel Imaging). This method uses a speckle image, that contrast value is analyzedusingImageJ or MATLAB software. To obtain the optimum speckle image contrast value, the arrival angle (laser angle) and capture angle (camera angle) must be adjusted properly. Obtained angle values that produce the optimum speckle image contrast, are at the arrival angle 40o and capture angle 30o at 60o data capture position. The average of the optimum contrast value is 1.2617 a.u. To simplify the speckle image processing, a speckle image contrast analysis application based on the GUI MATLAB was created. Obtained the measurement accuracy from the application is ranged from 99,99 % to 100.00%.